New Zealand financial sector assessment program : detailed assessment of observance--Basel core principles for effective banking supervision. (IMF country report ;, 2017)
The supervisory approach of the Reserve Bank of New Zealand (RBNZ) reflects the characteristics of the local banking industry and the authorities' goal to limit moral hazard by relying on market discipline and not offering deposit insurance. Banks offer traditional products, in a highly concentrated market, dominated by four subsidiaries of the four largest Australian banking groups. The RBNZ approach relies on three pillars: market discipline, based on public disclosure; self-discipline, based on bank directors' attestations of public information; and regulatory discipline, based on a simple and conservative regulatory framework, off-site monitoring, and disciplinary actions. It also relies on synergies with the Australian Prudential Regulation Authority (APRA) home-country supervision of Australian banks' operations in New Zealand. In practice, though, the RBNZ approach is in conflict with the Basel Core Principles for Effective Supervision (BCP) requirements, which expect granular regulatory guidance and on-site independent verification work by the supervisor. 1 The RBNZ aims to strengthen supervision while retaining its current approach.